Fertilizer micro-dosing and harvesting time of indigenous leafy vegetables affect in vitro antioxidant activities - Modoukpè I. Djibril Moussa; Adeola M. Alashi; Carole N. A. Sossa-Vihotogbé; P. B. Irénikatché Akponikpè; Mohamed N. Baco; André J. Djènontin; Rotimi E. Aluko; Noël H. Akissoé (Journal of Food Bioactives, 2019)
Plant nutrient management can influence the type and level of polyphenolic compounds within leafy vegetables. Therefore, we investigated the effects of fertilizer micro-dosing and harvest time on antioxidant activities of aqueous polyphenolic extracts from Amaranthus cruentus, Ocimum gratissimum and Solanum macrocarpon. Plants were cultivated using urea alone or combined with cattle manure for three staggered harvest periods. Polyphenolics profile (RP-HPLC), DPPH, hydroxyl and superoxide radical scavenging activities, ferric ion reducing power, ferrous ion chelation and inhibition of linoleic acid oxidation were determined. Polyphenolic contents of A. cruentus (caffeic acid, myricetin, quercetin and rutin) and O. gratissimum (catechin and gallic acid) as well as antioxidant activities of the vegetables extracts (except hydroxyl radical scavenging by A. cruentus) were fertilizer micro-dose and harvest timedependent. Thus, combination of both factors highlighted the screening of optimal farming conditions for these vegetables in order to get leaf extracts possessing higher polyphenolic contents and antioxidant activities.